Crowbar Resistance Setting and its Influence on DFIG Low Voltage Based on Characteristics - Li Shengqing; Yao Ming; Yuwen Zhang (IAES International Journal of Robotics and Automation (IJRA), 2017)
In the case of low voltage fault cases,doubly fed induction generator (DFIG) with Crowbar protection circuit to realize low voltage ride through (LVRT),and the choice of crowbar resistance of unit LVRT effects is very large.In this paper, from the DFIG wind power system steady state and transient mathematical model of voltage drop down, using space vector analysis method and Laplace transform, deduced the time domain transient current expressions of voltage drop Put forward the method for calculating the maximum fault current and the rotor side crowbar resistance setting method, solve the crowbar protection circuit for tilting rotor current and DC bus over-voltage problems. Numerical example and simulation shows that, The proposed method, effectively suppress the transient component of fault current, significantly improved the automation level of the wind power system.